Teachers Professional Development And Students' Academic Achievement In Public Senior Secondary School In Niger State, Nigeria - Olaifa, Adeseko Sunday; Ciroma, Usman Abdul; Olaifa, Ebunlomo Oreoluwa; Onikoyi, Olawale Abayomi; Shittu, Adesina Afeez (International Journal of Universal Education, 2025)
This study investigated teacher's professional development and students' academic achievement in public senior secondary schools in Niger State, Nigeria. The descriptive survey of the correlational type was adopted for the study. The population of this study comprised 7,825 Public Senior Secondary School Teachers. A sample of 367 teachers was selected using purposive and simple random sampling techniques. A researcher-designed instrument titled "Teacher's Professional Development and Students' Academic Achievement Questionnaire (TPDSAAQ) was utilised for data collection. The findings of this study revealed that; teachers' professional development programmes engaged in senior secondary schools in Niger State include seminars, workshops, conferences, online courses and peer observation. Similarly, the level of students' academic achievement in public senior secondary schools in Niger State, Nigeria is high. There is a significant relationship between teacher's professional development and students' academic achievement in public senior secondary schools in Niger State, Nigeria. It was recommended, among others, that the government prioritise sustaining and expanding teachers' professional development programs. Policymakers should regularly assess the effectiveness of teachers' professional development initiatives in improving classroom practice and student performance. Teachers should be encouraged to apply the strategies learned from professional development programs in the classroom, and structured follow-ups should be provided to provide ongoing support. School authorities should encourage and formalise peer observation programs, where teachers regularly observe each other's lessons and provide constructive feedback.